Integrating Fiscal Policy Mix and Environmental Policy in East Java's Circular Economy Development: A Multidimensional Approach Assessing Economic, Social, and Legal Factors - Nafis Dwi Kartiko (East Java Economic Journal, 2023)
This study aims to provide a more holistic understanding of how environmental and fiscal policies can complement each other to promote a circular economy in East Java. The method used in this study is panel data regression analysis using secondary data covering the period 2001-2020. Data were collected from government agencies such as the Ministry of Finance, the East Java Central Bureau of Statistics, the Ministry of Environment and Forestry, and the Supreme Audit Agency. The results show that environmental and fiscal policies significantly impact the circular economy in East Java. Environmental regulations, which include central and local government policies, promote the growth of the circular economy. The Regional Original Revenue (PAD) also plays an essential role in influencing the circular economy in the region. The proposed policy recommendations include the design of incentives to encourage the adoption of circular economy principles, the optimal allocation of special environmental and circular economy funds, the adaptation of education and training to the needs of the circular economy, the promotion of research and innovation in the circular economy, and the joint implementation of environmental regulations.